2017
DOI: 10.1111/avj.12610
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary unicystic ameloblastoma in a 6‐week‐old filly evaluated with computed tomography

Abstract: Surgical excision was not deemed feasible with an athletic future in mind and the owners elected to euthanase the filly. Histopathologically, the mass was consistent with unicystic ameloblastoma and was lined intermittently with palisading, columnar basal cells (ameloblast-like cells) overlying a zone containing stellate cells in loose stroma. To the authors' knowledge this is the first report of a CT scan of an equine ameloblastoma. Although histopathology was essential for definitive diagnosis, CT clearly de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Both the mare in this series, and in the previous report, 9 did not have a complete postmortem, therefore, metastases could not be excluded. Radiation therapy arrested growth of the mass for 6 months but was unsuccessful in diminishing the maxillary tumor growth in this case (5), even with prior surgical debulking. Surgical resection was performed in a previous case report of canine mandibular ameloblastic carcinomas, with no recurrence of the tumor.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Both the mare in this series, and in the previous report, 9 did not have a complete postmortem, therefore, metastases could not be excluded. Radiation therapy arrested growth of the mass for 6 months but was unsuccessful in diminishing the maxillary tumor growth in this case (5), even with prior surgical debulking. Surgical resection was performed in a previous case report of canine mandibular ameloblastic carcinomas, with no recurrence of the tumor.…”
Section: Discussionmentioning
confidence: 66%
“…4 They are predominantly found within the mandible of older horses, although they have also been reported in three foals. 4,5 These tumors can be discrete but can also be locally aggressive with extensive bone loss in advanced stages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 The filly had a growing mass over the right maxilla that was causing respiratory distress at exercise. Radiographs showed that the mass originated from the maxilla and was causing deviation of the nasal septum.…”
Section: Equinementioning
confidence: 99%
“…A case report shows the extraordinary computed tomography (CT) appearance of a maxillary ameloblastoma in a Thoroughbred foal . The filly had a growing mass over the right maxilla that was causing respiratory distress at exercise.…”
Section: Equinementioning
confidence: 99%